Effect of simvastatin on the extraction socket healing in the mandible of prednisolone-treated albino rat - Asmaa Fahem; Rania Hassan; Khaled El-Haddad (Ain Shams University, Faculty of Dentistry, 2024)
Aim: This work aimed to evaluate the possible prophylactic effect of using Simvastatin as adjunctive treatment to ameliorate the effects of using prednisolone on the healing of the albino rat mandibular molar extraction socket.Materials and Methods: 42 rats were equally divided into 3 groups (I: received distilled water, II received Prednisolone, III: received simvastatin + prednisolone via gastric tube). After 5 weeks, the mandibular 1st molar was extracted then each group was further subdivided into 2 subgroups depending on sacrifice time after extraction: (A: 10 days and B: 21 days). Mandibular molar areas were processed for histomorphometric and immunohistochemical examination using osteonectin marker. The cell counts and new bone area percentage were measured and statistically analyzed using T-test, ANOVA and post hoc tukey tests. Results: Prednisolone significantly decreased the area of new bone, osteoblasts and osteocytes count. Simvastatin had positive effects in the active osteoblasts and recent osteocytes cell counts marked by osteonectin staining and the new bone formation to a comparable level to the control group. The significant effects of Simvastatin on wound healing were indicated by statistical analysis of different parameters. Conclusions: Prednisolone adversely affected the extraction socket healing. Simvastatin leads to minimizing the effects of prednisolone by increasing the cellular count and bone formation. Keywords: Simvastatin, Extraction Socket, Prednisolone, Rats